Trust-Value Based Wireless Sensor Network Using Compressed Sensing - Anand, JV (Journal of Electronics and Informatics, 2020)
Wireless sensor networks have quickly paved way to novel ways of communication between two nodes. They consist of sensor nodes that have the capacity to sense, communicate and compute. If a particular node in a WSN is not able to transmit data to the base station, routing algorithms will move into action to direct the data from the node. The proposed work deals with a routing algorithm based on trust awareness and compression sensing data, to handle data routing in a clustered WSN. In general, when sensor nodes have reduced overhead, compressed sensing is utilized for data aggregation. In order to strike a balance between number of messages transmitted, hop count, distance of transmission and the optimal trusted path, many nature inspired optimisation methods have been developed over the years. However, trust-based retrieval of compressed data is executed at the base station amidst malicious nodes.